Urban Blue Spaces : Planning and Design for Water, Health and Well-Being. - Bell, Simon; Fleming, Lora E.; Grellier, James; Kuhlmann, Friedrich; Nieuwenhuijsen, Mark J.; White, Mathew P. (Milton : Taylor & Francis Group, 2021)
This book presents an evidence-based approach to landscape planning and design for urban blue spaces that maximises the benefits to human health and well-being. Over 200 full colour illustrations accompany the case study examples from geographic locations all over the world.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books